Trauma Providers' Perceptions of Frailty Assessment: A Mixed-Methods Analysis of Knowledge, Attitudes, and Beliefs. Issue 3 (March 2019) - Shoultz, Thomas H.; Moore, Megan; Reed, May J.; Kaplan, Stephen J.; Bentov, Itay; Hough, Catherine; Taitsman, Lisa A.; Mitchell, Steven H.; So, Grace E.; Arbabi, Saman; Phelan, Herb; Pham, Tam
Abstract : Objectives: Quality improvement in geriatric trauma depends on timely identification of frailty, yet little is known about providers' knowledge and beliefs about frailty assessment. This study sought to understand trauma providers' understanding, beliefs, and practices for frailty assessment. Methods: We developed a 20-question survey using the Health Belief Model of health behavior and surveyed physicians, advanced practice providers, and trainees on the trauma services at a single institution that does not use formal frailty screening of all injured seniors. Results were analyzed via mixed methods. Results: One hundred fifty-one providers completed the survey (response rate 92%). Respondents commonly included calendar age as an integral factor in their determinations of frailty but also included a variety of other factors, highlighting limited definitional consensus. Respondents perceived frailty as important to older adult patient outcomes, but assessment techniques were varied because only 24/151 respondents (16%) were familiar with current formal frailty assessment tools. Perceived barriers to performing a formal frailty screening on all injured older adults included the burdensome nature of assessment tools, insufficient training, and lack of time. When prompted for solutions, 20% of respondents recommended automation of the screening process by trained, dedicated team members. Conclusions: Providers seem to recognize the impact that a diagnosis of frailty has on outcomes, but most lack a working knowledge of how to assess for frailty syndrome. Some providers recommended screening by designated, formally trained personnel who could notify decision makers of a positive screen result. Abstract : This study used mixed methods to evaluate providers' understanding of a patient population to identify key barriers to more effective care in frail patients. The authors found that most providers at their level 1 urban trauma center considered frailty an important clinical factor; however, many providers were unsure of the definition or assessment tools and did not feel empowered to assess frailty. In the future, implementation of a systematic frailty screening process to address current gaps in identification of frail patients would facilitate the formulation of care plans aimed at improving patient-centered outcomes.